Efeitos tóxicos da exposição aguda e subaguda a fração acetato de etila da casca da Scutia buxifolia Reissk em camundongos - Silva, Andreia Regina Haas da (2014)
Plant belonging to the family Rhamnaceae, the Scutia buxifolia is a small tree. In Brazil occurs in Paraná, Santa Catarina and Rio Grande do Sul and in these places, is popularly known as coronilha . By infusing water in the bark and leaves, S. buxifolia it is used as a cardiotonic, antihypertensive and diuretic substance. This study aimed to evaluate the acute and subacute toxicity of the ethyl acetate fraction of the stem bark of S. buxifolia in male and female mice. As methodology guidelines of the Organization for Economic Cooperation and Development (OECD-guidelines 423 and 407). In the analysis of acute toxicity, a single dose of 2000 mg/kg of S. buxifolia was administered orally to both sexes mice. Mortality, biochemical and hematological parameters were evaluated. The study of subacute toxicity, the plant was administered orally to the animals, males and females, at doses of 100, 200 and 400 mg/kg/day for 28 days. Behavioral changes, body weight gain, food intake, biochemical, hematological and histological parameters were analyzed. In acute exposure, no behavioral changes were found. However, caused a decrease in platelet levels in mice and male and female reduction in leukocyte levels only in females. In subacute toxicity study, no behavioral changes were observed in body weight gain and food intake in mice of both sexes. There was a reduction in glucose levels in male mice treated with 200 and 400 mg/kg S. buxifolia and activity of aspartate aminotransferase (AST) was increased in treated male mice with S. buxifolia at the highest dose. In relation hematological parameters, male mice showed a reduction in hemoglobin (HGB) and hematocrit (HCT), when treated with 400 mg/kg of plant fraction. The females showed no change in biochemical and hematological parameters. Histopathological examination of liver tissue showed small changes that were consistent with the biochemical changes observed. Histopathological changes were also observed in the kidneys of animals treated with 400 mg/kg of plant fraction. As the evaluation of acute toxicity by oral administration ethyl acetate fraction from the bark of S. buxifolia of can be classified as safe (category 5), according to the OECD guide. However, the changes observed after subacute administration with high doses of extract, ethyl acetate fraction of the stem bark of S. buxifolia suggest that repeated administration of the plant fraction can cause liver, kidney and hematologic adverse effects.